Pengaruh Self-confidence Siswa Terhadap Kemampuan Pemecahan Masalah Matematika pada Kelas V Sekolah Dasar - Siti Musyarrofah; Siti Sahronih (CV. Akademi Merdeka, 2024)
This research uses a quantitative approach, with a survey method. The aim of the research is to determine the relationship between mathematical problem solving and students' self-confidence. The research population consisted of 52 students at SD Negeri Taman Kalijaga Permai. The data collection technique was purposive sampling. The instruments used are in the form of test sheets and questionnaires. The research results show that students' self-confidence is 0.105 and the significant value (sig) is 0.632. It can be concluded that there is a strong relationship between self-confidence and problem solving. So it can be concluded that students' self-confidence can influence the results of students' mathematical problem solving, especially in FPB and KPK material.